Revidiran seznam steklokrilcev (Lepidoptera: Sesiidae) Slovenije - Predovnik, Željko (Acta entomologica slovenica (Ljubljana), 2020)
Based on own research of the fauna of clearwing moths in the period 1998 - 2019, as well as data from museums collections, a new revised list of clearwing moths of Slovenia is presented, whereby a total of 44 species have been reliably confirmed. Comments are given on species that were not included in the new list due to insufficient references and lack of material evidence. I also discuss species that are present in the fauna of neighboring countries and may be expected in Slovenia. The revised list of clearwing moths of Slovenia is in line with recent changes in taxonomy in Europe.
Keywords: clearwing moths; favnistika; Lepidoptera; Sesiidae; Slovenia; Slovenija; steklokrilci; Žuželke